(3YQGFS CfXGQ GdCHcGQ hfaGFS eYGOf GdCSQGQs
(3ChdgG (B:s
(3GdMeO ddg (B( (3ef (B) (3jQaY OQLGJ ef jTGA HMLJg hCeQ HGdOYhI Edi SHjdI HGdMceI hGdehYXI s
(3BNQgG (B:s
(3hefg GdbjGS GdChd gh eG jJhba KHhJ EMOi ebOeJjg Ydi KHhJ GdfJjLI hbjd dJZGjQgeG HGdELeGd hGdJaUjd Yfg XGgQ GdMeO ddg Ydi GdEJeGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdg hbajI HGSe YdGeI HjQhJ GdTjN eMeO SYjO Hf eMeO Hc EjGS GdOeTbi CUdkG hGdHjQhJi ehdOkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs